Taxonomic revision of the moss salamander Nototriton barbouri (Schmidt (Caudata: Plethodontidae), with description of two new species from the Cordillera Nombre de Dios, Honduras - Townsend, Josiah H. (Zootaxa, 2016)
Moss salamanders (genus Nototriton) are represented in northern Central America by nine putative species: N. barbouri, N. brodiei, N. lignicola, N. limnospectator, N. mime, N. picucha, N. saslaya, N. stuarti, and N. tomamorum. I estimate the phylogenetic relationships for these species based on data from three mitochondrial gene fragments (16S, cytochrome b, and COI), and compare morphological variation among putative taxa. As evidenced here and in previous studies, the taxon N. barbouri is paraphyletic with respect to populations from the Cordillera Nombre de Dios in northern Honduras. I restrict this taxon to populations from the Sierra de Sulaco in central Yoro, Honduras, and describe two new species from the Cordillera Nombre de Dios.